Pengaruh Bauran Pemasaran 7p Terhadap Keputusan Nasabah Menggunakan Produk Tabungan Pada Pt. Bank Perekonomian Rakyat Lengayang Cabang Surantih Pesisir Selatan - Sophan Sophian; Yestri Ananta (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of the 7P marketing mix, which includes product, price, place, promotion, people, process, and physical evidence, on customers’ decisions to use savings products at PT BPR Lengayang Surantih Branch. The research method used is a quantitative approach with data collection techniques through the distribution of questionnaires to 97 respondents. The data analysis techniques include validity testing, reliability testing, and multiple linear regression analysis. The results of the study indicate that simultaneously the 7P marketing mix has a significant effect on customers’ decisions. Partially, the variables of product, price, place, and physical evidence have a positive and significant effect on customers’ decisions. Meanwhile, the variables of promotion, people, and process do not have a significant effect and even show a negative relationship, so the hypotheses related to these variables are rejected. This indicates that not all elements of the marketing mix have the same influence on customers’ decisions. Therefore, PT BPR Lengayang Surantih Branch is expected to focus more on improving product quality, setting competitive prices, choosing strategic locations, and enhancing physical evidence of services in order to increase customers’ decisions to use savings products.